Software para desenvolvimento de transformadores para equipamentos de eletrocirurgia - Paula, Jhonisson Ricardo de (2012)
This work describes a software that performs calculation and gives some tips about building and measuring transformers parameters up to 500 W till a few megahertz. The software emulates 3 models: the classical T model for low power and low frequency; the T model with output capacitance; and the complete delta-star model, for high frequency electronic transformers. This work aimed to create a tool for design of transformers, especially biomedical instrumentation output transformers, like the output electrosurgical device transformer. Tips like, for example, how to wrap the secondary coil to minimize intrinsic capacitance are presented to the software user. The software indicates the model according to input data or by user choice. The software is for free use and is programmed in Java language, so that, any person interested can use it. It will be available on the internet for free download. This software can work on all computers, desktops or mobiles, and on almost all operating systems, as long as the user has the virtual machine in his hardware. The user must insert the coefficients required to perform the calculations. After this insertion he must click on the calculation button, so the results and the impedance (modulus and phase) versus frequency graphs are seen on the screen. The user can additionally export an XY CSV (comma-separated values) data file. The software graphical output modulus and phase parts shows behavior of the input impedance (Zin) versus frequency. This makes possible for the user see the resonances and characteristic behavior of the transformer.